2015
DOI: 10.1007/s10971-015-3846-6
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Yb3+-doped YAG transparent ceramics by aqueous gelcasting

Abstract: In this work, Yb:YAG transparent ceramics were prepared through aqueous gel-casting forming technique. Single-phase Yb:YAG nanopowders with mean particle size of 170 nm were used to prepare Yb:YAG slurries. The rheological properties of Yb:YAG slurries were investigated as a function of pH value and the dispersant content. It was found that the maximum zeta potential was achieved at pH = 11.5 with 2 wt% dispersant content (based on the weight of Yb:YAG powders). And then, the stable slurries with different sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This refers also to LuPO 4 , whose high density (∼6.5 g/cm 3 ) makes it potentially attractive for some scintillation applications 1,12,16,17 . Transparency can be achieved not only in single crystals but also making high-density sintered materials, whose grains are separated by thin boundaries, while voids are absent [18][19][20] . However, high transparency of sintered materials can be achieved when they show optical isotropy.…”
Section: Introductionmentioning
confidence: 99%
“…This refers also to LuPO 4 , whose high density (∼6.5 g/cm 3 ) makes it potentially attractive for some scintillation applications 1,12,16,17 . Transparency can be achieved not only in single crystals but also making high-density sintered materials, whose grains are separated by thin boundaries, while voids are absent [18][19][20] . However, high transparency of sintered materials can be achieved when they show optical isotropy.…”
Section: Introductionmentioning
confidence: 99%
“… The nanopowders were uniaxially pressed into Φ 20 mm disks at 10 MPa followed by cold isostatic pressing (CIP) at 200 MPa. The gelcasting procedure in this study was similar to that reported in the previous publication . First, premixed solution was prepared by adding 10 wt% monomer (Methacrylamide, MAM), 1 wt% cross‐linking agent (N,N′‐methylenebisacrylamide, MBAM) and different amount of dispersant (Polyacrylic acid, PAA) to the deionized water.…”
Section: Methodsmentioning
confidence: 99%
“…However, although the gelcasting technology has been developed for decades and it has unique advantages in the preparation of transparent ceramics, there are still some problems that have not been completely solved up to now . The transparent ceramics prepared by gelcasting were generally small round wafer or rectangular strip (about 10‐30 mm in diameter or length) . Even if some ceramics were prepared into large sizes, they were usually the round or rectangular and could not achieve large‐size rods with a huge special aspect ratio (>10) or extreme dimension size .…”
Section: Introductionmentioning
confidence: 99%
“…21,24,25 The transparent ceramics prepared by gelcasting were generally small round wafer or rectangular strip (about 10-30 mm in diameter or length). [26][27][28][29] Even if some ceramics were prepared into large sizes, they were usually the round or rectangular and could not achieve large-size rods with a huge special aspect ratio (>10) or extreme dimension size. 30,31 Large-sized rod ceramics needed the higher requirements for the initial strength of green body in order to transport and dry.…”
Section: Introductionmentioning
confidence: 99%